SARS-CoV-2 Employ BSG/CD147 and ACE2 Receptors to Directly Infect Human Induced Pluripotent Stem Cell-Derived Kidney Podocytes - Kalejaiye, Titilola D.; Bhattacharya, Rohan; Burt, Morgan A.; Travieso, Tatianna; Okafor, Arinze E.; Mou, Xingrui; Blasi, Maria; Musah, Samira (Frontiers in Cell and Developmental Biology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes the Coronavirus disease 2019 (COVID-19), which has resulted in over 5.9 million deaths worldwide. While cells in the respiratory system are the initial target of SARS-CoV-2, there is mounting evidence that COVID-19 is a multi-organ disease. Still, the direct affinity of SARS-CoV-2 for cells in other organs such as the kidneys, which are often targeted in severe COVID-19, remains poorly understood. We employed a human induced pluripotent stem (iPS) cell-derived model to investigate the affinity of SARS-CoV-2 for kidney glomerular podocytes, and examined the expression of host factors for binding and processing of the virus. We studied cellular uptake of the live SARS-CoV-2 virus as well as a pseudotyped virus. Infection of podocytes with live SARS-CoV-2 or spike-pseudotyped lentiviral particles revealed cellular uptake even at low multiplicity of infection (MOI) of 0.01. We found that direct infection of human iPS cell-derived podocytes by SARS-CoV-2 virus can cause cell death and podocyte foot process retraction, a hallmark of podocytopathies and progressive glomerular diseases including collapsing glomerulopathy observed in patients with severe COVID-19 disease. We identified BSG/CD147 and ACE2 receptors as key mediators of spike binding activity in human iPS cell-derived podocytes. These results show that SARS-CoV-2 can infect kidney glomerular podocytes in vitro via multiple binding interactions and partners, which may underlie the high affinity of SARS-CoV-2 for kidney tissues. This stem cell-derived model is potentially useful for kidney-specific antiviral drug screening and mechanistic studies of COVID-19 organotropism.